KISAH-KISAH (QAṢAṢ) DALAM AL-QUR’AN PERSPEKTIF I’JĀZ - Aqidatur Rofiqoh; Ibnu Hajar Ansori (QOF, 2017)
The Qur’an is a holy book that is always interesting to be examined from all sides: from the beauty of the language used to the contained meaning; from the form of writing to the variety of readings; including some matters related to the subject matter of the Qur’an. All these aspects if examined in depth, will lead us to the conclusion that the Qur’an is a miracle, as well as prove that the risks of Muhammad Saw is true. One of the main content of the Qur’an is the stories. Judging from the time of occurrence, the stories can be divided into three categories. First, the stories of previous prophets that were so difficult for historians to uncover, as the ‘Ā d and Thamū d and the city of Iram they were proud of; the story of Pharaoh and his destruction and the power of Allā h to immortalize his body; story of Aṣḥāb al-Kahf and so forth. Second, the notice of the Messenger of Allah concerning the state of his people, including the conspiracy of the unbelievers and the munafiq who were about to kill him. Third, the news about something that will happen like preaching about the victory of the Muslims in the war badar, victory of the army of Rum on Persi also the news about the coming of Judgment Day and human condition at that time. The truth of the stories is certain. It became one amongst the evidence of miracles. In addition, the presenting of these stories is packed with beautiful language with high literary value, thus further strengthening the miracles of the Qur’an and proving that it really comes from Allah Swt, not Muhammad’s engineering.